Integrating Cultural Diversity in Rural Classrooms: Pathways to Inclusive and Democratic Education - Andrew Skourdoumbis (Nurul Jadid University, 2024)
This study explores integrating cultural diversity and empowering student voices in classroom teaching practices. The aim is to examine how teachers incorporate cultural backgrounds into their lesson plans and classroom activities to foster an inclusive and democratic learning environment. A qualitative research design with a case study approach was employed to gather detailed insights into these practices. Data collection involved interviews with eight teachers and several students, direct classroom observations, and document analysis, including lesson plans and teaching notes. The study reveals that teachers in Indonesia actively integrate students' cultural backgrounds into the curriculum, using socio-cultural themes to create a more inclusive classroom atmosphere. Teachers empower students by encouraging them to voice their opinions during discussions and actively participate in decision-making. However, the study also identifies a gap in the consistent application of deliberative democracy principles, with many classrooms still dominated by a teacher-centered approach. The findings suggest that while efforts are being made to create a more inclusive and participatory learning environment, there is a need for further development in fully adopting deliberative democracy in educational practices. The implications of this study emphasize the importance of integrating cultural diversity and fostering student agency to enhance student engagement, motivation, and achievement in education.